Cationic liposome decorated with cyclic RGD peptide for targeted delivery of anti-STAT3 siRNA to melanoma cancer cells. (28th May 2022) - Khabazian, Ehsan; Vakhshiteh, Faezeh; Norouzi, Parisa; Fatahi, Yousef; Dinarvand, Rassoul; Atyabi, Fatemeh
Abstract: Gene therapy is regarded as a valuable strategy for efficient cancer treatment. However, the design of effective delivery systems that can deliver gene materials such as siRNA specifically to the tumour tissues plays a pivotal role in cancer therapy. For this reason, a targeted cationic liposome for melanoma treatment was developed. This system consists of cyclic RGD peptide conjugated to DSPE-PEG2000, cholesterol, DOTAP and DSPC as cationic and neutral lipids, respectively. Cyclic RGD was selected based on speculation that cyclic RGD would effectively transport anti-signal transducer and activator of transcription 3 (STAT3) siRNA into melanoma cell via integrin receptors. The prepared liposomes provided excellent stability against electrolyte and serum nucleases. Targeted liposomes remarkably exhibited higher cellular internalisation in comparison with the non-targeted system in flow cytometry and confocal microscopy. Furthermore, incorporating peptide on the surface of liposomes resulted in considerably high cytotoxicity, a 2.1-times raise in apoptosis induction, and a significantly enhanced STAT3 gene suppression as compared with the corresponding non-targeted formulation on B16F10 murine melanoma cells. Whole-body imaging confirmed the more significant tumour accumulation of targeted liposomes in B16F10 melanoma xenograft tumour-bearing mice. Consequently, c-RGD peptide modified liposome suggests a promising option for specific siRNA delivery into melanoma cells.